2018
DOI: 10.1002/ajh.25115
|View full text |Cite
|
Sign up to set email alerts
|

A case series describing causes of death in pregnant women with sickle cell disease in a low‐resource setting

Abstract: Sickle cell disease (SCD) is most prevalent in sub-Saharan Africa with 15,000 newborns per year in Ghana. 1,2 Pregnant women with SCD have increased risks of both SCD-specific and pregnancy-related complications, compared to pregnant women without SCD. 3 In a recent meta-analysis, our team reported that SCD in pregnancy increases the risk of maternal death by over 20-fold compared to pregnant women without SCD, in lowand middle-income countries. 4 In sub-Saharan Africa, maternal death rate of SCD is 7%-12%, 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…The definition of acute pain episode as in our previous publications was maintained. 3,4,6 During the postpartum period, "if the patient was able to judge whether the pain was of the type usually associated with crisis and reported such pain, this was considered appropriate evidence of an acute pain episode. 5 " The total number of acute pain episodes requiring hospitalization was confirmed with a chart review.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of acute pain episode as in our previous publications was maintained. 3,4,6 During the postpartum period, "if the patient was able to judge whether the pain was of the type usually associated with crisis and reported such pain, this was considered appropriate evidence of an acute pain episode. 5 " The total number of acute pain episodes requiring hospitalization was confirmed with a chart review.…”
mentioning
confidence: 99%
“…The definition of ACS as in our previous publications was maintained. 3,4,6 The research obstetricians and hematologists adjudicated all participants admitted for suspected ACS events. A consensus agreement was reached to determine the diagnosis of ACS.…”
mentioning
confidence: 99%
“…During the month‐long training in Nashville the team also systematically reviewed the literature to conduct a pooled analysis on maternal and perinatal outcomes in pregnancies associated with SCD . Also, the team conducted a combined retrospective (January 2010 to April 2015) and prospective (May 2015 to December 2016) case series of all maternal deaths in women with SCD at KBTH . This process highlighted service delivery, failures and challenges to delivering improved care while allowing for providers to develop new, acceptable and feasible solutions. Creation of a multidisciplinary SCD obstetric team : In 2015, the clinic expanded to a multidisciplinary team including 3 local hematologists, 2 midwives, 2 laboratory scientists, a pediatrician, a dual‐certified anesthesiologist and pulmonologist, including SCD experts from Vanderbilt University and an obstetrician and gynecologist from Duke University Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review and meta‐analysis our team demonstrated that SCD is associated with an increased risk of maternal death compared to women without SCD in low‐resource settings (odds ratio [OR] 22.8 [95% CI 14.7‐35.5], P < .001) . Acute chest syndrome (ACS) is a major cause of death among pregnant women with SCD . Other adverse maternal outcomes in women with SCD include hypertensive disorders of pregnancy (preeclampsia, eclampsia), severe anemia, urinary tract infections, and increased odds of both antenatal and postnatal acute pain episodes .…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy and the postpartum period are associated with increased ACS risk. ACS is the most common cause of acute respiratory failure and death in pregnant or postpartum SCD patients in low-resource settings, with ACS responsible for >60% of the deaths in pregnant women with SCD in this population ( 31 , 51 ). In Ghana, a multidisciplinary approach using a combined obstetric and hematology team was effective in reducing ACS incidence and all-cause maternal mortality ( 52 ).…”
Section: Acsmentioning
confidence: 99%